Investigating molecular masses formed during the heat treatment of petroleum pitches by mass spectrometry - Pereira, Maria Helena; Castro, Luiz de; Michel, Ricardo (Publishing House of Lviv Polytechnic National University, 2013)
Mass spectrometry was used to characterize isotropic and anisotropic pitches as well as the parent heavy petroleum oil in order to investigate the molecular mass distributions (MMD) and changes during the heat treatment process. Sample preparation and matrix choice have a strong influence on MMD and results confirmed the oligomeric nature and the increasing molecular sizes as heat treatment proceeds. За допомогою мас-спектрометрії охарактеризовані ізотропні і анізотропні пеки,а також вихідна важка мінеральна олива з метою встановлення розподілу молекулярних мас (РММ) та змін, що відбуваються під час термооброблення. Показано,що метод приготування проб і вибір матриці мають значний вплив на РММ. Одержані результати підтверджують олігомерну природу пеків та збільшення розмірів молекул при термічному обробленні.
Дослідження мас-спектроскопічним методом молекулярних мас нафтових пеків одержаних внаслідок термооброблення
Keywords: petroleum pitch; heavy oil; mass spectrometry; MALDI-TOF-MS; polyaromatic hydrocarbon; нафтовий пек; важка олива; мас-спектрометрія; поліароматичні вуглеводні